2020
DOI: 10.7717/peerj.9960
|View full text |Cite
|
Sign up to set email alerts
|

Co-application of bio-fertilizer and salicylic acid improves growth, photosynthetic pigments and stress tolerance in wheat under drought stress

Abstract: Drought stress hampers the growth and productivity of wheat crop worldwide. Thus far, different strategies have been proposed to improve drought tolerance in wheat but the combined application of plant growth-promoting rhizobacteria formulated bio-fertilizer (BF) and salicylic acid (SA) has not been thoroughly explored yet. Therefore, a pot experiment was conducted to observe the effect of SA, BF, and their combination on wheat plants under optimal and drought stress conditions. Seeds priming was done with BF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 59 publications
4
26
0
1
Order By: Relevance
“…Phytopathogenic fungi severely reduce the yield of agricultural products, and the use of biological fertilizer offers a sustainable way of avoiding this problem [7]. The ability to produce diverse secondary metabolic compounds is the most outstanding biocontrol feature of the Bacillus species.…”
Section: Introductionmentioning
confidence: 99%
“…Phytopathogenic fungi severely reduce the yield of agricultural products, and the use of biological fertilizer offers a sustainable way of avoiding this problem [7]. The ability to produce diverse secondary metabolic compounds is the most outstanding biocontrol feature of the Bacillus species.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we proposed that VOCs produced by P. pseudoalcaligenes induce a systemic response in maize plants against drought stress conditions. The positive impact of PGPR inoculation on drought stress mitigation on plants has already been reported in many studies (Amna et al, 2020;Azmat et al, 2020;Ghosh et al, 2018;Ilyas et al, 2020;Yasmin et al, 2017). Cho et al (2008) has demonstrated the role of bacterial VOCs (BVOCs) on drought stress mitigation in Arabidopsis thaliana.…”
Section: Discussionmentioning
confidence: 81%
“…Secondly, VOCs exposed seedlings further augmented the ROS scavenging machinery and exhibited higher activity of SOD, POD, CAT, APX, PPO, and PAL and reduced the drought stress than non‐exposed control. The role of PGPR in the alleviation of drought stress by augmenting the ROS scavenging enzyme system is well documented in the literature (Azmat et al, 2020; Ilyas et al, 2020; Khan et al, 2020; SkZ et al, 2018; Yasmin et al, 2017). However, for the first‐time current study showed BVOCs‐mediated alleviation of drought stress by modulating ROS scavenging machinery.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations